N.I. PIROGOV – FOUNDER OF RUSSIAN MILITARY MEDICAL DOCTRINE - I. M. Tchig; I. V. Karpenko (Сеченовский вестник, 2010)
Contribution of N.I. Pirogov into development of military medical service and military surgery is discussed